Development Of Internal Recruitment Methods Based On Local Wisdom: Sociocultural Approach At - Kosim, Rijal Muhamad; Hariyanto, Teguh; Tamlekha, Tamlekha; Napisah, Nina; Erihadiana, Mohamad (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
Internal recruitment based on local wisdom with a sociocultural approach is a strategic approach to improve the quality of educators and education at SMK Ma'arif NU Pangandaran. This article aims to identify and develop internal recruitment methods that integrate the values of Ahlus Sunnah wal Jama'ah (Aswaja) and local wisdom in the process of selection, promotion, and development of the workforce. This research uses a qualitative approach with a case study at SMK Ma'arif NU Pangandaran with in-depth interviews with policy makers, observation of the recruitment process, and analysis of institutional documents. The results of the study show that the internal recruitment method based on local wisdom not only strengthens the identity of the institution as part of Nahdlatul Ulama (NU) but also increases the loyalty, dedication, and quality of educators. This recruitment involves values such as tawasuth (moderate), tasamuh (tolerant), tawazun (balanced), as well as the active participation of the NU community in the selection and coaching process. Positive impacts include increasing the harmonization of relationships between schools and the community, preserving NU traditions, and improving the quality of education based on local character